Arrhythmic Phenotypes Are a Defining Feature of Dilated Cardiomyopathy-Associated SCN5A Variants: A Systematic Review. (24th December 2021) - Peters, Stacey; Thompson, Bryony A.; Perrin, Mark; James, Paul; Zentner, Dominica; Kalman, Jonathan M.; Vandenberg, Jamie I.; Fatkin, Diane
Abstract : Background: Variants in the SCN5A gene, that encodes the cardiac sodium channel, Nav1.5, are associated with a highly arrhythmogenic form of dilated cardiomyopathy (DCM). Our aim was to review the phenotypes, natural history, functional effects, and treatment outcomes of DCM-associated rare SCN5A variants. Methods: A systematic review of reported DCM-associated rare SCN5A variants was undertaken using PubMed and Embase. Results: Eighteen SCN5A rare variants in 29 families with DCM (173 affected individuals) were identified. Eleven variants had undergone experimental evaluation, with 7 of these resulting in increased sustained current flow during the action potential (eg, increased window current) and at resting membrane potentials (eg, creation of a new gating pore current). These variants were located in transmembrane voltage-sensing domains and had a consistent phenotype characterized by frequent multifocal narrow and broad complex ventricular premature beats (VPB; 72% of affected relatives), ventricular arrhythmias (33%), atrial arrhythmias (32%), sudden cardiac death (13%), and DCM (56%). This VPB-predominant phenotype was not seen with 1 variant that increased late sodium current, or with variants that reduced peak current density or had mixed effects. In the latter groups, affected individuals mainly showed sinus node dysfunction, conduction defects, and atrial arrhythmias, with infrequent VPB and ventricular arrhythmias. DCM did not occur in the absence of arrhythmias for any variant. Twelve studies (23 total patients) reported treatment success in the VPB-predominant cardiomyopathy using sodium channel-blocking drug therapy. Conclusions: SCN5A variants can present with a diverse spectrum of primary arrhythmic features. A majority of DCM-associated variants cause a multifocal VPB-predominant cardiomyopathy that is reversible with sodium channel blocking drug therapy. Early recognition of the distinctive phenotype and prompt genetic testing to identify variant carriers are needed. Our findings have implications for interpretation and management of SCN5A variants found in DCM patients with and without arrhythmias.